Simultaneous Determination of Irinotecan Hydrochloride and its Related Compounds by High Performance Liquid Chromatography Using Ultraviolet Detection - Mohammadi, Ali; Esmaeili, Farnaz; Dinarvand, Rassoul; Atyabi, Fatemeh; B. Walker, Roderick (Asian Journal of Chemistry, 2010)
A new simple, precise and accurate high performance liquid chromatography (HPLC) method was developed and validated for the simultaneous determination of irinotecan (CPT-11) and two related compounds viz., 7-ethyl-10-hydroxycamptothecin (SN-38) and camptothecin (CPT) in pharmaceutical dosage forms. Chromatography was accomplished using a reversed-phase C18 column and ultraviolet (UV) detection and an isocratic mobile phase consisting of 3 % v/v triethylammonium acetate buffer (pH 3) and acetonitrile (70:30 v/v). The linear range of quantitation for all the compounds was 0.1-10 μg/mL. The limit of quantitation for all the compounds ranged between 0.01-0.05 μg/mL. The method has the requisite accuracy, selectivity, sensitivity and precision to assay of CPT-11 and related compounds in pharmaceutical dosage forms and bulk API.